Specialna vojna - Jenuš, Gregor (Annales. Series historia et sociologia, 2017)
The article deals with the activities of the postwar Yugoslav communist one-party regime in the establishment of a security system on the Slovenian (Yugoslav) border. Based on the analysis of archival records from the Archives of the Republic of Slovenia in Ljubljana, Military archives in Belgrade and literature, the authors analyze how the system of state border protection in Slovenia (Yugoslavia) towards its western democratic neighbors Austria and Italy has been developed. They furthermore present activities of the Yugoslav state security service in recruiting agents for the so called "Special war" against "external" and "internal enemies" of the post-war Yugoslav communist one-party regime. By analyzing the statistics of the Yugoslav internal affairs bodies, they present the dimensions of the fl ight of population and reasons for it; they also present the activities of the internal affairs bodies in order to prevent them. On the case of the Hermagoras Society in Klagenfurt (Austria), they present the attempt of the Yugoslav State security service to infi ltrate the society in 1986 and 1988 in order to sabotage the work of the political emigration abroad.
Keywords: agents; agentura; border control; nadzor meje; Slovenia; Slovenian political emigration; Slovenija; slovenska politična emigracija; Služba državne varnosti; special war; specialna vojna; State Security Service